Tsetse salivary gland hypertrophy virus: hope or hindrance for tsetse control? - Adly M M Abd-Alla; Andrew G Parker; Marc J B Vreysen; Max Bergoin (Public Library of Science (PLoS), 2011)
MANY SPECIES OF TSETSE FLIES (DIPTERA: Glossinidae) are infected with a virus that causes salivary gland hypertrophy (SGH), and flies with SGH symptoms have a reduced fecundity and fertility. The prevalence of SGH in wild tsetse populations is usually very low (0.2%-5%), but higher prevalence rates (15.2%) have been observed occasionally. The successful eradication of a Glossina austeni population from Unguja Island (Zanzibar) using an area-wide integrated pest management approach with a sterile insect technique (SIT) component (1994-1997) encouraged several African countries, including Ethiopia, to incorporate the SIT in their national tsetse control programs. A large facility to produce tsetse flies for SIT application in Ethiopia was inaugurated in 2007. To support this project, a Glossina pallidipes colony originating from Ethiopia was successfully established in 1996, but later up to 85% of adult flies displayed symptoms of SGH. As a result, the colony declined and became extinct by 2002. The difficulties experienced with the rearing of G. pallidipes, epitomized by the collapse of the G. pallidipes colony originating from Ethiopia, prompted the urgent need to develop management strategies for the salivary gland hypertrophy virus (SGHV) for this species. As a first step to identify suitable management strategies, the virus isolated from G. pallidipes (GpSGHV) was recently sequenced and research was initiated on virus transmission and pathology. Different approaches to prevent virus replication and its horizontal transmission during blood feeding have been proposed. These include the use of antiviral drugs such as acyclovir and valacyclovir added to the blood for feeding or the use of antibodies against SGHV virion proteins. In addition, preliminary attempts to silence the expression of an essential viral protein using RNA interference will be discussed.